2‐AG limits Theiler's virus induced acute neuroinflammation by modulating microglia and promoting MDSCs. Issue 7 (27th February 2018) - Mecha, Miriam; Feliú, Ana; Machín, Isabel; Cordero, Cesar; Carrillo‐Salinas, Francisco; Mestre, Leyre; Hernández‐Torres, Gloria; Ortega‐Gutiérrez, Silvia; López‐Rodríguez, María L; de Castro, Fernando; Clemente, Diego; Guaza, Carmen
Abstract: The innate immune response is mediated by primary immune modulators such as cytokines and chemokines that together with immune cells and resident glia orchestrate CNS immunity and inflammation. Growing evidence supports that the endocannabinoid 2‐arachidonoylglycerol (2‐AG) exerts protective actions in CNS injury models. Here, we used the acute phase of Theiler's virus induced demyelination disease (TMEV‐IDD) as a model of acute neuroinflammation to investigate whether 2‐AG modifies the brain innate immune responses to TMEV and CNS leukocyte trafficking. 2‐AG or the inhibition of its hydrolysis diminished the reactivity and number of microglia at the TMEV injection site reducing their morphological complexity and modulating them towards an anti‐inflammatory state via CB2 receptors. Indeed, 2‐AG dampened the infiltration of immune cells into the CNS and inhibited their egress from the spleen, resulting in long‐term beneficial effects at the chronic phase of the disease. Intriguingly, it is not a generalized action over leukocytes since 2‐AG increased the presence and suppressive potency of myeloid derived suppressor cells (MDSCs) in the brain resulting in higher apoptotic CD4 + T cells at the injection site. Together, these data suggest a robust modulatory effect in the peripheral and central immunity by 2‐AG and highlight the interest of modulating endogenous cannabinoids to regulate CNS inflammatory conditions. Main Points: The endocannabinoid 2‐AG limits brain acute inflammation induced by TMEV infection. 2‐AG modulates microglia towards an anti‐inflammatory state via CB2 receptors. 2‐AG reduces brain infiltrates and increases the presence and suppressive power of MDSCs.